C2-Alkylation of N-pyrimidylindole with vinylsilane via cobalt-catalyzed C–H bond activation - Ding, Zhenhua; Yoshikai, Naohiko (Beilstein Journal of Organic Chemistry, 2012)
Direct C2-alkylation of an indole bearing a readily removable N-pyrimidyl group with a vinylsilane was achieved by using a cobalt catalyst generated in situ from CoBr2, bathocuproine, and cyclohexylmagnesium bromide. The reaction allows coupling between a series of N-pyrimidylindoles and vinylsilanes at a mild reaction temperature of 60 °C, affording the corresponding alkylated indoles in moderate to good yields.
Keywords: alkylation; C–H functionalization; cobalt; indole; vinylsilane